PENGARUH PEMAHAMAN KONSEP GHIBAH TERHADAP KESALEHAN SOSIAL PADA IBU-IBU RT 01/ RW 04 DUSUN KUKULU DESA CIPANCAR - Dian Sukmara; Lilis Elis Nawati (STAI Sebelas April Sumedang, 2021)
Ghibah according to Sharia is telling about someone who is not in a place with something he hates. It's good to mention bodily disgrace, heredity, morals, actions, religious matters, or world affairs. Until, even though all that was mentioned was something he didn't like about her clothes. Therefore, by carrying out this research, the author aims to find out: 1) Understanding the concept of backbiting among the mothers of Rt 01/ Rw 04 Kukulu Hamlet, Cipancar Village, 2) Social piety among the mothers of Rt 01/ Rw 04 Kukulu Hamlet, Cipancar Village, 3) The influence of understanding the concept of backbiting on social piety among women in Rt 01/ Rw 04 Kukulu Hamlet, Cipancar Village. This research uses a quantitative research approach with a quantitative descriptive method, correlational research type, with observation data collection, questionnaires and documentation. It was carried out at Rt 01/ Rw 04 Kukulu Hamlet, Cipancar Village, South Sumedang District, Sumedang Regency with the research subjects being mothers who were at Rt 01/ Rw 04 Kukulu Hamlet, Cipancar Village with a total of 38 people. Based on the results of this research, the influence of understanding the concept of backbiting on social piety in the women of Rt 01/Rw 04 Kukulu Hamlet, Cipancar Village. And after testing it with the help of the SPSS application, the author was able to find out the magnitude of the influence that the concept of backbiting has on social piety, which is 0.088, equal to 8.8%, while the remaining 91.2% is influenced by other factors such as social, economic factors, or possibly the habits of the community's environment.